2022
DOI: 10.3390/ijerph19031235
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Equality and Equity. A Scoping Review of Interventions Directed towards Promoting Access to Leisure Time Physical Activity for Children and Youth

Abstract: Promoting access to leisure time physical activity (LTPA) opportunities for children and youth is crucial to promote public health. Yet, ensuring sustainable interventions in this field requires theoretically informed approaches to guide the processes of developing, implementing and evaluating LTPA programs. The objective of this review was to examine how concepts of equality and equity have been operationalized in LTPA interventions for children and youth in order to identify facilitating factors and barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…This is the case in the increasing number of studies describing the inequity in access to sports for children and youths and how inclusion in sporting communities may be promoted (cf. review by Hjort and Agergaard 2022). Recent studies have demonstrated that it is particularly children and youths from low socio-economic and minority ethnic backgrounds, along with disabled children and youths, that do not have access to sport to the same extent as other children and youths (Andersen and Bakken 2018;Elofsson et al 2019;Rask et al 2020;Strandbu et al 2019;Strandbu and Bakken 2024).…”
Section: Current Research On Children's Rights To and In Sportmentioning
confidence: 99%
“…This is the case in the increasing number of studies describing the inequity in access to sports for children and youths and how inclusion in sporting communities may be promoted (cf. review by Hjort and Agergaard 2022). Recent studies have demonstrated that it is particularly children and youths from low socio-economic and minority ethnic backgrounds, along with disabled children and youths, that do not have access to sport to the same extent as other children and youths (Andersen and Bakken 2018;Elofsson et al 2019;Rask et al 2020;Strandbu et al 2019;Strandbu and Bakken 2024).…”
Section: Current Research On Children's Rights To and In Sportmentioning
confidence: 99%
“…Reducing structural inequality in sport requires more than just money [121], a sustainable whole-of-system approach must be adopted to allow schools, policymakers, and parents to work together to improve youth engagement in sport. Recent literature exemplifies how 'locally owned' community sport interventions are particularly efficacious in empowering youth and transcending several societal inequities related to PA [124]. From the point of view of children and adolescents, it is important to note that sport provides them invaluable opportunities for civic engagement, improvement of cognitive/emotional functioning and subsequently, improved physical and psychological well-being [125], along with opportunities to break down cultural barriers, build community identity, establish friendships, develop networks, and reduce social isolation [126].…”
Section: Social Justice-sport and Food Security As Tools?mentioning
confidence: 99%
“…A similar range of approaches has been described in relation to sports programs for adolescents, distinguishing between the universal equality approach directed towards promoting sports participation among large groups of adolescents, and the more specific targeted equity approach, which focuses on making sports accessible for the adolescents that need the most help (Hjort and Agergaard 2022). Yet, to our knowledge, no publications have set out to reconceptualize vulnerability to develop encompassing descriptions and adequate support to participants in health-promoting programs that offer physical activity and sport.…”
Section: Health Research On Vulnerabilitymentioning
confidence: 99%